Validação da técnica de macacos planos na avaliação da resistência de alvenaria existente executada com blocos vazados de concreto - Ferreira Júnior, Jairo Borges (2020)
The flat jack method is used as non-destructive test, on site, on masonry structures to obtain more accurate data. This method is already standardized internationally by ASTM and RILEM, however, the studies, standards, and jacks available on the subject, refer to masonry with solid elements, such as bricks and stones. This work aims to validate and improve the technique of flat jacks in the evaluation of the compressive strength of modern existing masonry, being developed a new equipment in the literature, the first flat jack with double flaps for testing structural masonry with hollow concrete blocks. The new equipment and the test methodology were successfully developed, adapting the deformability test (double plane jack), carrying out the tests on a real structural masonry construction with hollow concrete blocks and validating this technique as non-destructive. It was demonstrated how to manufacture and calibrate the new jacks, and how to perform and analyze the tests, comparing the results found in laboratory tests, made available by the company responsible for the construction. The research is motivated by the standardization of tests with the use of flat jacks in structures with hollow blocks masonry, facilitating the execution, cost reduction and the time spent with tests to determine the characteristics of the hollow concrete blocks, mainly, without needing to break the masonry wall.